Obsessive-Compulsive Disorder (OCD) is still an unrecognised disorder: A study on the recognition of OCD in psychiatric outpatients - Wahl, K.; Kordon, A.; Kuelz, K.A.; Voderholzer, U.; Hohagen, F.; Zurowski, B. (European psychiatry, 2010)
The study aims to investigate the recognition of patients with Obsessive-Compulsive Disorder (OCD) in psychiatric outpatients. A total of 2282 outpatients seen at 14 different psychiatric clinics in South Germany were asked to participate in the study. Five hundred and eighty-nine (30%) of the original 2282 patients met screening criteria for OCD, and of those, 237 (42%) participated in the final interview including DSM-IV diagnosis, and comorbidity. Sixty-nine of 589 participating patients who screened positively for obsessive symptoms actually had an Obsessive-Compulsive Disorder. Only 19 (28%) of the outpatients diagnosed with OCD according to DSM-IV criteria were also given this diagnosis by their consultant. The psychopathology scores indicated that the OCD patients had clinically relevant OCD with a mean Yale-Brown Obsessive Compulsive Score (Y-BOCS) of 17.5 (± 5.4), and a mean Clinical Global Impression Score (CGI) of 5.2 (± 1.2). In outpatient clinics over 70% of OCD patients remain unrecognised and thus untreated by consultants. Screening questions provide a rapid way of identifying those who may have OCD and should be incorporated into every mental state examination by consultants.